Narcolepsy: Pathophysiology and Neuropsychological Changes - Angela Naumann; Irene Daum (Behavioural Neurology)
Narcolepsy is now recognized as a distinctive disorder with specific pathophysiology and neurochemical abnormalities. Findings on the role of the neuropeptide hypocretin are opening new avenues of research and new strategies for therapy. Recently, neuropsychological and electrophysiological studies have provided evidence for reduced memory performance on standard memory tests in addition to subjective complaints of forgetfulness which may be related to changes in attentional processing. Further studies are, however, necessary to clarify the neuropsychological profile in narcolepsy. This review focuses on the recent advances in understanding narcolepsy.